Impact of particle flux on the vertical distribution and diversity of size-fractionated prokaryotic communities in two East Antarctic polynyas - Puigcorbé, Viena; Ruiz-González, Clara; Masqué, Pere; Gasol, Josep M. (Frontiers in Microbiology, 2023)
Antarctic polynyas are highly productive open water areas surrounded by ice where extensive phytoplankton blooms occur, but little is known about how these surface blooms influence carbon fluxes and prokaryotic communities from deeper waters. By sequencing the 16S rRNA gene, we explored the vertical connectivity of the prokaryotic assemblages associated to particles of three different sizes in several stations in two polynyas with different surface productivity, and we linked it to the magnitude of the particle export fluxes measured using thorium-234 (234Th) as particle tracer. Between the sunlit and the mesopelagic layers (700 m depth) in the three size fractions we observed compositional changes in the prokaryotic communities, which were mostly dominated by Flavobacteriia, Alphaproteobacteria and Gammaproteobacteria. Interestingly, the vertical differences between bacterial communities associated with the largest particles decreased with increasing 234Th export fluxes, indicating a higher downward transport of surface prokaryotes in the most productive polynya. This was accompanied by a higher proportion of surface prokaryotic taxa detected in deep particle-attached microbial communities in the station with the highest 234Th export flux. Our results support recent studies evidencing links between surface productivity and deep prokaryotic communities and provide the first evidence of sinking particles acting as vectors of microbial diversity to depth in Antarctic polynyas, highlighting the direct influence of particle export in shaping the prokaryotic communities of mesopelagic waters.